Climate Change and Urbanization in Arid Regions - Portnoy, Boris A; Paz, Shlomit (Annals of Arid Zone, 2016)
Ongoing global climate change, which manifests itself in the greater inter-annual variability of precipitation, rising summer temperatures, and increasing periods of droughts, is likely to affect the pace of arid land urbanization in three distinct ways: (a) increasing migration of desert nomads into urban areas; (b) restructuring of regional economies towards reducing the relative share of traditional water-intensive agriculture, and (c) increasing the number of urban settlements in arid regions due to expansion of deserts towards arid land fringes. The present paper looks into the interaction between the climate change and urbanization in arid regions and formulates recommendations for urban and regional development policy aimed at a more sustained urban growth in arid regions. Key words: Deserts, arid zones. urbanization. climate change.